Clinical outcomes and cortical reserve in adrenal histoplasmosis—A retrospective follow‐up study of 40 patients. (10th February 2019) - Singh, Mahaveer; Chandy, David D.; Bharani, Tamnay; Marak, Rungmei S. K.; Yadav, Subhash; Dabadghao, Preeti; Gupta, Sushil; Sahoo, Saroj K.; Pandey, Rakesh; Bhatia, Eesh
Summary: Objective: Detailed studies of Addison's disease resulting from disseminated adrenal histoplasmosis (AH) are not available. We describe the presentation and prognosis of AH and cortisol status before and after antifungal therapy. Design: Single‐centre retrospective hospital‐based study of 40 consecutive adults with AH [39 males; age (mean ± SD) 53 ± 11 years] was conducted between 2006 and 2018. The median duration of follow‐up was 2.5 years (range 0.2‐12 years). Patients and methods: AH was diagnosed by bilateral adrenal enlargement on CT scan and presence of Histoplasma by histology and/or culture of biopsied adrenal tissue. All patients received oral itraconazole and, if required, amphotericin B as per guidelines. ACTH‐stimulated serum cortisol (normal > 500 nmol/L) was measured in 38 patients at diagnosis and re‐tested after one year of antifungal therapy in 21 patients. Results: Seventy‐three per cent of patients had primary adrenal insufficiency (PAI) and one‐third had an adrenal crisis at presentation. HIV antibody was negative in all patients. Of the 29 patients who completed antifungal therapy, 25 (86%) were in remission at last follow‐up. Overall, 8 (20%) patients died: three had a sudden death, four had severe histoplasmosis and one died due to adrenal crisis. No patient with PAI became eucortisolemic on re‐testing after one year of antifungal therapy. Of the eight patients with normal cortisol at diagnosis, two developed adrenal insufficiency on follow‐up. Conclusion: All patients with AH tested negative for HIV antibody. While patients achieved a high rate of clinical remission after antifungal therapy, overall mortality was significant. Cortisol insufficiency did not normalize despite treatment.